Successful Treatment of Concomitant Pleural Mucosa-Associated Lymphoid Tissue Lymphoma and Monoclonal Gammopathy of Undetermined Significance with Lenalidomide, Rituximab, and Dexamethasone - Uemura, Yoshiki; Maeda, Risa; Saegusa, Hiroyoshi (Case Reports in Hematology, 2022)
Concomitant plasma cell and B cell neoplasms in a single patient have been infrequently reported. It is known that the prognosis of these patients is worse than that of patients with single-disease onset. Generally, the chemotherapy specific for each disease is provided sequentially. It has been suggested that the specific chemotherapy for lymphoma could lead to the occurrence of refractory multiple myeloma (MM). We present a case with the concomitant occurrence of mucosa-associated lymphoid tissue (MALT) lymphoma and monoclonal gammopathy of undetermined significance (MGUS). MGUS does not usually require aggressive treatment. However, the potential adverse effects of MGUS on the treatment course of the B cell lymphoma were concerning. Therefore, we explored a new therapeutic approach that is simultaneously effective against both diseases. Combination therapy of lenalidomide (LEN) and rituximab (RIT) gained indication for follicular lymphoma and MALT lymphoma recently. LEN is also a key drug in MM treatment. Both diseases in our patient were effectively treated with the combination of LEN, RIT, and dexamethasone. With this combination therapy, we expect a prognostic improvement in concomitant MM and B cell lymphoma cases.